EKSPLORASI ETNOMATEMATIKA TERHADAP MASJID SYAHRUN NUR SIPIROK SEBAGAI MEDIA PENYAMPAIAN KONSEP GEOMETRI - Siregar, Salbiah; Hasibuan, Eka Khairani (Universitas Swadaya Gunung Jati., 2024)
Ethnomathematics is mathematics found in culture. The aim of this research is to explore mathematical concepts at the Syahrun Nur Sipirok Mosque. The research method used is a qualitative method with an ethnographic approach. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, conclusions. The results of this research are that at the Syahrun Nur Sipirok mosque there are mathematical concepts in the form of flat shapes and spatial shapes which are viewed from the architecture and ornamental motifs, namely triangles, squares, parallelograms, blocks, rhombuses and hexagons